2016
DOI: 10.1590/s1980-65742016000100013
|View full text |Cite
|
Sign up to set email alerts
|

The effects of foot morphology and anthropometry on unipodal postural control

Abstract: Abstract--The maintenance of posture is a constant challenge for the body, as it requires rapid and accurate responses to unforeseen disturbances, which are needed to prevent falls and maintain balance. The purpose of the present study was to compare different types of plantar arch in relation to postural balance, and analyze the relationships between variations the plantar arch and anthropometric characteristics of the feet with unipedal static balance. We evaluated 100 men and women between the ages of 20 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
(14 reference statements)
2
8
0
1
Order By: Relevance
“…In the female group, the reaction time was faster and the larger the foot size, the greater the maximum excursion. In the male group, the narrower the foot, the worse the control of anteroposterior direction, corroborating previous studies 4,11,12,13 which claim that the increase in base of support size improves postural balance. These data are related to a larger area of contact between the feet and the platform surface, and do not necessarily indicate intrinsic changes in balance, especially since there were no changes in movement speeds.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the female group, the reaction time was faster and the larger the foot size, the greater the maximum excursion. In the male group, the narrower the foot, the worse the control of anteroposterior direction, corroborating previous studies 4,11,12,13 which claim that the increase in base of support size improves postural balance. These data are related to a larger area of contact between the feet and the platform surface, and do not necessarily indicate intrinsic changes in balance, especially since there were no changes in movement speeds.…”
Section: Discussionsupporting
confidence: 89%
“…These data are related to a larger area of contact between the feet and the platform surface, and do not necessarily indicate intrinsic changes in balance, especially since there were no changes in movement speeds. 11 The lower the BMD the greater the movement speed and the worse the control of speed in the mediolateral and anteroposterior directions. These data are similar to a previous study in semi-static condition.…”
Section: Discussionmentioning
confidence: 99%
“…Our study states that neither the foot length nor the foot width influences postural balance. These observations matched with Alonso et al, [28], but they had conducted the study using unipedal standing balance task. Our findings contradicted with those of Chiari et al [12] in which foot width showed positive correlation with postural balance.…”
Section: Discussionsupporting
confidence: 87%
“…However, the local RPE was able to identify differences in internal load in "Just Dance" game, whereas the overall RPE was similar between the load conditions. It has been suggested that RPE is generated independently of physiological responses 20 , especially in continuous exercises 19 , because the external load is maintained, while the internal load is perceived to increase by the individual. Moreover, the load attached bilaterally to the ankle may have emphasized the lower limb efforts, i.e., a local exercise.…”
Section: Discussionmentioning
confidence: 99%
“…HR and EMG) during exercises with an incremental load in cycling 16,17 and running 18 , these results do not follow the same pattern during continuous load exercises. For instance, 30 minutes of circuit-training at fixed HR induced RPE increase throughout the exercise 19 . This inconsistency between HR stabilization and RPE increase is due to the perception of the internal load being greater as the exercise progresses, despite the maintenance of the external load 15 .…”
Section: Introductionmentioning
confidence: 99%